Uji Kekuatan Bending Pipa Komposit Jute-Epoxy pada Perlakuan Rendaman Air Panas - Purna Wirama, I Wayan; Astika, I Made; Ary Subagia, I.D.G (Jurnal Energi Dan Manufaktur, 2022)
The main purpose of this study was to determine the comparison of the bending strength of composite pipes when treated with hot water. In this study, composite pipes were made using woven sacks and tied with an epoxy matrix which was molded using the VARTM (Vacuum Assisted Resin Transfer Molding) method. Jute fiber laminated composite on epoxy binder is made by laminated 3 layers with fiber direction 45 0 and has a thickness of 2.55 mm, the jute-epoxy composite pipe will be treated with heat treatment. Then tested on bending loading. The results of this study were the bending stress and strain on the control specimen compared to the heat treated specimen, an increase in the strain of the heat treatment specimen was 0.007 [MPa], this was due to the heat treatment temperature on the specimen which caused a change in the properties of the specimen itself, which was initially a brittle specimen changes to plastic. Meanwhile, the value of bending stress and modulus of elasticity on control specimens and heat treatment specimens. The obtained stress on the control composite pipe is 67.946 [MPa] with a modulus of elasticity of 10.398 [GPa]. While the heat-treated composite pipe has a bending stress of 28.613 [MPa] with an elastic modulus of 2.225 [GPa].